Time and space variations of the O2/N2 ratio in the troposphere over Japan and estimation of the global CO2 budget for the period 2000–2010 - Shigeyuki Ishidoya; Shuji Aoki; Daisuke Goto; Takakiyo Nakazawa; Shoichi Taguchi; Prabir K. Patra (Tellus: Series B, Chemical and Physical Meteorology, 2012)
Systematic measurements of the atmospheric O2/N2 ratio have been made using aircraft and ground-based stations in Japan since 1999. The observed seasonal cycles of the O2/N2 ratio and atmospheric potential oxygen (APO) vary almost in opposite phase to that of the CO2 concentration at all altitudes, and their amplitudes and phases are generally reduced and delayed, respectively, with increasing altitude. Simulations of APO using two atmospheric transport models reproduce general features of the observed seasonal cycle, but both models fail to reproduce the phase at an altitude ranging from 8 km to the tropopause. By analysing the observed secular trends of APO and CO2 concentration, and assuming a global net oceanic O2 outgassing of 0.2±0.5 GtC yr−1, we estimate global average terrestrial biospheric and oceanic CO2 uptake for the period 2000–2010 to be 1.0±0.8 and 2.5±0.7 GtC yr−1, respectively.